Recommendations regarding the military-economic substantiation of operational training measures in the Armed Forces of Ukraine - Semenenko, Oleh; Pampukha, Ihor; Holovanov, Andrii; Poberezhets, Tetiana; Onofriichuk, Andrii; Semenenko, Liliia (Social Development and Security, 2023)
Purpose: is to formulate recommendations regarding the military-economic justification of operational training measures in the Armed Forces of Ukraine based on the indicators of their total cost. Method: the main methods of research are the methods of statistical analysis; military-economic analysis, comparison, formalization, abstraction and conjunctural analysis (thinking). Findings: a system of basic measures of operational training has been formed; the specifics of holding such events in NATO member states are determined; an algorithm for calculating the total cost of operational training measures in the Armed Forces of Ukraine was formed; a number of practical recommendations regarding the military-economic substantiation of operational training measures in the Armed Forces of Ukraine have been defined. Theoretical implications: the main results of the research on the topic of the article are an approach to estimating the total cost of operational training in the Armed Forces of Ukraine and recommendations on the military-economic justification of operational training measures during the formation of training plans of the Armed Forces of Ukraine. Paper type: descriptive and calculation-analytical.